PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING BERBANTUAN MEDIA GAMBAR UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KREATIF MATEMATIS DAN SELF CONFIDENCE SISWA - Sumiati, Ketut; Yumiati, Yumiati; Sutiarso, Sugeng (Jurnal Pendidikan Dasar, 2022)
The learning process at SD Negeri 1 Sidorejo is included in the criteria of not being implemented where the learning process carried out by the teacher is not in accordance with the RPP prepared so that the teacher has not fully implemented the learning process in the 2013 Curriculum. This study aims to determine the effect of problem solving learning models assisted by image media on mathematical creative thinking skills and self confidence. This study uses a quantitative approach and includes Quasi Experiment research and in this study uses test questions and questionnaires. Based on the results of the study, the output results of the Test of Between-Subjects Effects showed that the problem solving learning model assisted by image media on mathematical creative thinking showed a sig value of 0.000 <0.05 so it was concluded that the problem solving learning model assisted by image media was better in improving creative thinking skills. mathematical. Problem solving learning model assisted by image media on students' self-confidence obtained the value of Sig. 0.000 <0.05, it can be concluded that the problem solving learning model assisted by picture media is better in increasing students' self-confidence. Based on the Manova test, it shows a sig value of 0.000 <0.05. So it can be concluded that the problem solving learning model assisted by image media is better in improving students' mathematical creative thinking skills and self-confidence.